Suicide intervention among aging network providers. Issue 6 (3rd June 2022) - Mize, Mary Chase Breedlove; Shannonhouse, Laura R.; Fullen, Matthew C.; Gilbride, Dennis; Barrio Minton, Casey
ABSTRACT: Older adults are at risk for mental health concerns, such as social isolation and suicide. Risk factors to suicide among older adults, such as loneliness and social isolation, may be impacted by the COVID-19 pandemic. Gatekeepers in the community are a significant source of identification and referral of older adults at risk of mental and physical health concerns. In this study, we sought to discover whether natural helpers in the Aging Service Network (ASN), including volunteers and providers ( n = 93) obtain and utilize suicide-intervention skills with older adults who receive home-delivered meals (HDM) after being trained in a 14-hour evidenced based training. Paired-sample t -tests yielded significant results at pre- and post-test measures of suicide intervention response skill acquisition, and over 19% of trained participants reported using suicide intervention skills over six months. Implications for future training and research are discussed.